NATURE AND ORIGIN OF ECLOGITE XENOLITHS FROM KIMBERLITES - Jacob D.E. (My University, 2004)
Eclogites from the Earth's mantle found in kimberlites provide important information on craton formation and ancient geodynamic processes because such eclogites are mostly Archean in age. They have equilibrated over a range of temperatures and pressures throughout the subcratonic mantle and some are diamond-bearing. Most mantle eclogites are bimineralic (omphacite and garnet) rarely with accessory rutiles. Contrary to their overall mineralogical simplicity, their broadly basaltic-picritic bulk compositions cover a large range and overlap with (but are not identical to) much younger lower grade eclogites from orogenic massifs. The majority of mantle eclogites have trace element geochemical features that require an origin from plagioclase-bearing protoliths and oxygen isotopic characteristics consistent with seawater alteration of oceanic crust. Therefore, most suites of eclogite xenoliths from kimberlites can be satisfactorily explained as samples of subducted oceanic crust. In contrast, eclogite xenoliths from Kuruman, South Africa and Koidu, Sierra Leone stem from protoliths that were picritic cumulates from intermediate pressures (1–2 Ga) and were subsequently transposed to higher pressures within the subcratonic mantle, consistent with craton growth via island arc collisions. None of the eclogite suites can be satisfactorily explained by an origin as high pressure cumulates from primary melts from garnet peridotite.
Keywords: Eclogites; Xenoliths; Major elements; Trace elements; Isotopes; Mantle